CHALLENGES TO THE ENACTMENT OF THE ELIMINATION OF SEXUAL VIOLENCE BILL - Nina Nurmila (HUMANISMA : Journal of Gender Studies, 2019)
Indonesia currently has only one criminal law, Kitab Undang-Undang Hukum Pidana (KUHP), which was enacted and inherited from our colonial government. There has been an effort to amend this law but up until now the amendment of this law is not enacted yet. In this law, there are only two types of sexual violence which have legal protection: rape and sexual molestation (pencabulan), while in the current reality, based on the reported cases to partners of Komnas Perempuan from 2001-2011, there are 15 types of sexual violence; and the number of sexual violence cases has been increasing. As a result, it is difficult for victims of the 15 types of sexual violence to have legal protection. This shows the existing hole in the lex generalis KUHP, which needs to be filled in by lex specialis law which specifically addresses sexual violence. Based on the need for legal protection for victims of various types of sexual violence and to protect women’s human rights, Komnas Perempuan and her partners have drafted the Elimination of Sexual Violence Bill since 2014. This Bill has become one of the priorities of the national legislation program since 2016, after the incidence of a gang rape to a school age child in Bengkulu. However, up until the end of September 2019, this Bill was not enacted yet. In addition, there has been currently opposition to this Bill from the conservative group, accusing that this Bill legalizes zina (extra marital sexual relationship) and LGBT.  This paper aims at elaborating the background, aims, contents and challenges to the enactment of the Elimination of Sexual Violence Bill. I will argue that this Bill offers both procedural and substantive justice for women and the marginalized groups, the majority victims of sexual violence.